Cutaneous Presentation of T-Cell Prolymphocytic Leukemia Mimicking Dermatomyositis. (July 2021) - Ingrasci, Giuseppe; Diaz-Perez, Julio; Verne, Sebastian; Romanelli, Paolo; Yosipovitch, Gil
Abstract : Abstract: T-cell prolymphocytic leukemia (TPLL) is a rare form of leukemia by T lymphocytes at a post-thymic intermediate stage of development with an α/β immunophenotype. Facial involvement is common in TPLL and displays significant heterogeneity of the lesions' description and location. TPLL also contains a wide array of histology findings, cell cytology, and molecular studies. Here, we describe a TPLL patient who presented with an ill-defined erythematous patch involving the right axilla progressing to the left axilla, upper back, and face that resembled dermatomyositis. The diagnosis of TPLL was established using flow cytometry of bone marrow and peripheral blood, and histopathology of the involved skin. Dermatologists should be aware of these unique features.